Elevating the Role of the Outdoor Environment for Adolescent Wellbeing in Everyday Life - Wales, Mark; Mårtensson, Fredrika; Hoff, Eva; Jansson, Märit (Frontiers in Psychology, 2022)
In light of concerns about adolescent mental health, there is a need to identify and examine potential pathways to well-being in their daily lives. Outdoor environments can offer multiple pathways to well-being through opportunities for restoration, physical activity and socialising. However, urbanisation and new lifestyles revolving around the home and the internet are changing young people’s access, use and relationship to the outdoor environment. The authors point out how the research related to adolescents’ outdoor environments is generally not treated with the same level of importance or as comprehensively as that for younger children. The aim of this paper is to pave the way for research and planning initiatives on everyday outdoor environments promoting the well-being of adolescents and the authors suggest ways in which perspectives from developmental psychology might inform the study of adolescent’s outdoor environments. The paper concludes by calling for an elevated focus on the role of outdoor environments in adolescents’ everyday lives as a source of well-being and more research that makes clear the specific attributes, activities and experiences related to places outdoors which make adolescents feel good.